Structural and Functional Characterization of the BcsG Subunit of the Cellulose Synthase in Salmonella typhimurium. Issue 18 (14th September 2018) - Sun, Lei; Vella, Peter; Schnell, Robert; Polyakova, Anna; Bourenkov, Gleb; Li, Fengyang; Cimdins, Annika; Schneider, Thomas R.; Lindqvist, Ylva; Galperin, Michael Y.; Schneider, Gunter; Römling, Ute
Abstract: Many bacteria secrete cellulose, which forms the structural basis for bacterial multicellular aggregates, termed biofilms. The cellulose synthase complex of Salmonella typhimurium consists of the catalytic subunits BcsA and BcsB and several auxiliary subunits that are encoded by two divergently transcribed operons, bcsRQABZC and bcsEFG . Expression of the bcsEFG operon is required for full-scale cellulose production, but the functions of its products are not fully understood. This work aimed to characterize the BcsG subunit of the cellulose synthase, which consists of an N-terminal transmembrane fragment and a C-terminal domain in the periplasm. Deletion of the bcsG gene substantially decreased the total amount of BcsA and cellulose production. BcsA levels were partially restored by the expression of the transmembrane segment, whereas restoration of cellulose production required the presence of the C-terminal periplasmic domain and its characteristic metal-binding residues. The high-resolution crystal structure of the periplasmic domain characterized BcsG as a member of the alkaline phosphatase/sulfatase superfamily of metalloenzymes, containing a conserved Zn 2+ -binding site. Sequence and structural comparisons showed that BcsG belongs to a specific family within alkaline phosphatase-like enzymes, which includes bacterial Zn 2+ -dependent lipopolysaccharide phosphoethanolamine transferases such as MCR-1 (colistin resistance protein), EptA, and EptC and the Mn 2+ -dependent lipoteichoic acid synthase (phosphoglycerol transferase) LtaS. These enzymes use the phospholipids phosphatidylethanolamine and phosphatidylglycerol, respectively, as substrates. These data are consistent with the recently discovered phosphoethanolamine modification of cellulose by BcsG and show that its membrane-bound and periplasmic parts play distinct roles in the assembly of the functional cellulose synthase and cellulose production. Graphical Abstract: Unlabelled Image Highlights: BcsG subunit of cellulose synthase is required for full-scale cellulose production. BcsG affects cellulose production via at least two distinct molecular mechanisms. Transmembrane part of BcsG is required for proper production of the BcsA subunit. The periplasmic domain of BcsG has the alkaline phosphatase superfamily structure. Crystal structure of the BcsG periplasmic domain shows a single active-site Zn ion.